PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL SISWA SMA NEGERI WILAYAH KABUPATEN PANDEGLANG - BANTEN - E. Nita Prianti (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2020)
This research was carried out aiming to pursue a goal one of which is to determine the extent of the influence of learning motivation on student achievement. With a strong motivation in students will certainly be able to increase interest and willingness in learning to guarantee the desired learning achievement in the subject of learning. the method used in this study is the correlation method which is part of the type of quantitative research. The population in this study were students of class XI of SMA Negeri Pandeglang with a total of 720 students with a total sample of 180 students taken as research data by random sampling. The results obtained there is a significant influence of learning motivation on the Social Science Learning Achievement of high school students this proves by the acquisition of Thitung = 4,372 and Sig 0,000 <0.05. Learning motivation variable contributed 32.65% to the learning achievements of Social Sciences of Pandeglang Public High School students. Thus based on the results of the data obtained there is an influence of learning motivation on student achievement in SMA Negeri Pandeglang.